PENERAPAN PENGGUNAAN APLIKASI SIMPERADES (SISTEM MONITORING PERIKANAN DESA SUNGAI DUREN) DALAM PENGELOLAAN BUMDES MANDIRI DI DESA SUNGAI DUREN KECAMATAN JAMBI LUAR KOTA KABUPATEN MUARO JAMBI - Anisa Purnamasari; Nurhayani, Nurhayani; Putri Intan Suri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of the SIMPERADES application in managing BUMDes Mandiri in Sungai Duren Village, Jambi Luar Kota District, Muaro Jambi Regency. The main problem addressed in this research is that administrative management and record-keeping of BUMDes were previously conducted manually, which potentially led to disorganized data, delays in report preparation, recording errors, and low work efficiency among managers. This study aims to identify the development of BUMDes Mandiri in Sungai Duren Village and to analyze the effectiveness of the SIMPERADES application in supporting administrative record-keeping. The research method used is descriptive, with data collection techniques including observation, interviews, documentation, and questionnaires. The respondents consisted of 15 individuals, including BUMDes managers and community members. Data were analyzed through Likert scale score recapitulation and effectiveness percentage calculations. The results show that BUMDes Mandiri Sungai Duren continues to operate through its fisheries business unit, although its development has not been optimal. BUMDes income decreased from IDR 28,295,000 in 2024 to IDR 27,309,000 in 2025, representing a decline of IDR 986,000 or 3.48%. Meanwhile, the evaluation of the SIMPERADES application resulted in a total score of 535 out of a maximum of 750, yielding an effectiveness level of 71.33%, which falls into the effective category. Thus, the SIMPERADES application is able to improve efficiency, accuracy, and reliability in administrative record-keeping of BUMDes Mandiri Sungai Duren, as well as support more organized, transparent, and sustainable village business management. These findings indicate that simple digitalization tailored to local needs can serve as a practical solution to overcome the limitations of manual record-keeping and strengthen data-driven decision-making processes. However, the application still requires continuous assistance and periodic evaluation to optimize its benefits in the future